Diversity, genetic structure, and hybridization in Pinus arizonica and P. durangensis populations - Morales-Nieto, Carlos Raúl; Siqueiros-Candia, Minerva; Álvarez-Holguín, Alan; Gil-Vega, Katia del Carmen; Corrales-Lerma, Raúl; Martínez-Salvador, Martín (Instituto de Ecología, A.C., 2021)
The evaluation of diversity, genetic structure, and the identification of introgressive hybridization may contribute to designing strategies to preserve the genetic richness of forest species. Likewise, the genetic richness contributes significantly to the adaptation of these species to adverse factors or new environmental conditions, such as climate change. Therefore, this study assessed the diversity, genetic structure, and hybridization capacity in Pinus arizonica y P. durangensis population located in Chihuahua, Mexico. Trees from three populations were analyzed through AFLP (Amplified Fragment Length Polymorphism) molecular markers. Results reveled wide genetic diversity [Shannon Index (I) = 0.37] in both species. In addition, populations showed genetic differentiation (p<0.05) in both evaluated species. However, such differences among populations explained less than 10% of the total variation. The southern population presented a greater differentiation compared to the others, which could have been generated by the canyons in this region, identified as a barrier to gene flow. The 39% of the analyzed trees of both species presented a genetic introgression of the other species, which means they come from hybrid ancestors. Given the genetic differences among populations, reforestation programs with P. arizonica and P. durangensis should use local materials. Furthermore, the hybridization potential of these species should be considered when selecting seed stands or plus trees.